Coordinated Regulation of Hypocotyl Cell Elongation by Light and Ethylene through a Microtubule Destabilizing Protein. Issue 1 (8th January 2018) - Ma, Qianqian; Wang, Xiaohong; Sun, Jingbo; Mao, Tonglin
Abstract : Light and ethylene mediate hypocotyl cell elongation by coordinating the expression of microtubule-destabilizing protein MDP60 in Arabidopsis. Abstract: Precise regulation of hypocotyl cell elongation is essential for plant growth and survival. Light suppresses hypocotyl elongation by degrading transcription factor phytochrome-interacting factor 3 (PIF3), whereas the phytohormone ethylene promotes hypocotyl elongation by activating PIF3. However, the underlying mechanisms regarding how these two pathways coordinate downstream effectors to mediate hypocotyl elongation are largely unclear. In this study, we identified the novel Microtubule-Destabilizing Protein 60 (MDP60), which plays a positive role in hypocotyl cell elongation in Arabidopsis ( Arabidopsis thaliana ); this effect is mediated through PIF3. Ethylene signaling up-regulates MDP60 expression via PIF3 binding to the MDP60 promoter. MDP60 loss-of-function mutants exhibit much shorter hypocotyls, whereas MDP60 overexpression significantly promotes hypocotyl cell elongation when grown in light compared to the control. MDP60 protein binds to microtubules in vitro and in vivo. The organization of cortical microtubules was significantly disrupted in mdp60 mutant cells and MDP60 -overexpressing seedlings. These findings indicate that MDP60 is an important mediator of hypocotyl cell elongation. This study reveals a mechanism in which light and ethylene signaling coordinate MDP60 expression to modulate hypocotyl cell elongation by altering cortical microtubules in Arabidopsis.